2014
DOI: 10.3109/08820538.2014.981551
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Ultra-Widefield Imaging with the Optos Optomap Compared with Indirect Ophthalmoscopy in the Setting of Non-Traumatic Rhegmatogenous Retinal Detachment

Abstract: Ultra-widefield imaging is a useful adjunct for documentation of rhegmatogenous retinal detachments and their postoperative repair. However, detection of retinal holes, tears, and postoperative scarring is poor, especially in the inferior and superior periphery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
0
32
2
Order By: Relevance
“…However, in non-KPro eyes, the authors have previously found that the Optos Optomap provides good detection and documentation of retinal detachments but is suboptimal for detecting retinal holes, tears, and other more subtle pathology, especially in the superior and inferior periphery. 30 In addition, UWF images were not directly compared with B-scan ultrasonography in this study. Although UWF images were able to sufficiently characterize vitreoretinal pathology in all but 1 case in this study, future directions would include a prospective trial directly comparing the ability of UWF imaging and B-scan ultrasonography to detect pathology and complement the clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…However, in non-KPro eyes, the authors have previously found that the Optos Optomap provides good detection and documentation of retinal detachments but is suboptimal for detecting retinal holes, tears, and other more subtle pathology, especially in the superior and inferior periphery. 30 In addition, UWF images were not directly compared with B-scan ultrasonography in this study. Although UWF images were able to sufficiently characterize vitreoretinal pathology in all but 1 case in this study, future directions would include a prospective trial directly comparing the ability of UWF imaging and B-scan ultrasonography to detect pathology and complement the clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-field imaging may be used to supplement fundus examination for characterizing and documenting retinal detachments [7,43]. Use of wide-field systems in the diagnosis and evaluation of retinal detachments is, however, controversial.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…63 In a retrospective study involving 36 eyes of 34 patients, wide-field more precisely documented the extent of retinal detachments in 13.9 % of cases, but failed to detect retinal holes in the superior and inferior quadrants in 11.1 % and 19.4 % of cases, respectively. 64 Retinopexy was not detected superiorly and inferiorly in 19.4 % of cases. Finally, a third study found moderate sensitivity for lesions posterior to the equator and low sensitivity anterior to the equator.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…Finally, a third study found moderate sensitivity for lesions posterior to the equator and low sensitivity anterior to the equator. 64 Specifically, for lesions posterior to the equator, sensitivity overall was 74 %, and 76 % for lesions requiring treatment, whereas for lesions anterior to the equator, sensitivity overall was 45 % and 36 % for treatable lesions. Specificity was 85 %.…”
Section: Retinal Detachmentmentioning
confidence: 99%